The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1007/s12262-012-0785-0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study on the Variations in the Branching Pattern of Internal Iliac Artery

Abstract: The internal iliac artery (IIA) arises from the common iliac artery at the level of the sacroiliac joint. It descends as trunk, divides into anterior and posterior divisions. From the anterior division it gives superior vesical, obturator, middle rectal, inferior vesical, inferior gluteal, and internal pudendal arteries. In females, inferior vesical artery is replaced by vaginal artery and gives an additional branch, uterine artery. The branches from the posterior division are ilio lumbar, lateral sacral, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 6 publications
3
12
1
Order By: Relevance
“…Hence, understanding anatomical variation of IIA is essential for surgeons to apply the IIA ligature to prevent hemorrhages following by pelvic surgeries, hysterectomies and orthopedic surgeries related to hip joint. Previous studies show that the level of origin of IIA is variable and dependent on the length of the common iliac artery and the level of division of IIA 5 . Typically, the origin of the IIA is between L5 and the upper border of S1 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, understanding anatomical variation of IIA is essential for surgeons to apply the IIA ligature to prevent hemorrhages following by pelvic surgeries, hysterectomies and orthopedic surgeries related to hip joint. Previous studies show that the level of origin of IIA is variable and dependent on the length of the common iliac artery and the level of division of IIA 5 . Typically, the origin of the IIA is between L5 and the upper border of S1 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Mamatha et al. 2 investigated 50 formalin fixed bisected pelvises irrespective of side and sex. While the origin of the ILA from the main trunk of the IIA was reported as a rare variation (6%), the additional origins of the LSA and SGA from the trunk were not observed in that study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, superior gluteal artery and other branches of the posterior division arise from the same trunk in a majority of the patients (62%), bearing an average length of 2.7 cm from the point of bifurcation of the common iliac artery (ranging between 2-3.5 cm). 3,4 This cadaveric dissection study found the distance between the bifurcation of the common iliac artery and the origin of the superior gluteal artery to be 3.1 cm. For most patients, the ligation of the internal iliac artery 3 cm away from the bifurcation of the common iliac artery is a safe idea.…”
mentioning
confidence: 94%